Innovative choledochoscope for simulation based training in resource limited setting. (January 2023) - Sarkar, Sucheta; De, Uditangshu; Manna, Saurav; De, Utpal
Intraoperative choledochoscopy is on the rise. Simulated training is essential for proper handling of the instrument during laparoscopic bile duct exploration. The article describes a low budget innovative choledochoscope for simulated training in low resource setting.